START-UP ECOSYSTEM: THE DRIVING FORCE OF DIGITAL INNOVATION IN ECONOMY 5.0 - Caroline Caroline (CV. Adiba Aisha Amira, 2025)
This article discusses the important role of the start-up ecosystem as the main driver of digital innovation in the Economy 5.0 era. By utilising advanced technologies such as artificial intelligence (AI), the Internet of Things (IoT), and blockchain, start-ups are able to produce innovative solutions that can improve productivity and quality of life. Support from the government and the private sector, such as friendly regulations, tax incentives, and access to funding, plays a crucial role in the development of this ecosystem. Collaboration between start-ups, educational institutions, and large companies is also a key factor in accelerating the adoption of technology and innovation. Through comprehensive support and effective collaboration, the start-up ecosystem can be the main driving force in digital transformation and sustainable economic development, which is inclusive and innovation-based. This article emphasises the importance of all these elements in creating an environment that supports the growth of start-ups and leads us towards a more dynamic future economy.